Freedom and Domination : A Historical Critique of Civilization - Rüstow, Alexander, 1885-1963 (Book collections on Project MUSE., 1980)
Presented here is a condensed translation of Alexander Rustow's three-volume Ortsbestimmung der Gegenwart. This monumental work was widely acclaimed by critics throughout Europe as a major contribution to both historical and sociological scholarship. Recognized as one of the foremost exponents of neoliberal thought, and thus as one of the intellectual authors of West Germany's economic miracle," Rustow--in his magnum opus--tried to determine what social patterns and trends of thought enhance the human condition and what other patterns and trends lead to repression and barbarism. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905